2021
DOI: 10.1111/ddi.13392
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dependency in abundance of Queen conch, Aliger gigas, in the Caribbean, indicates the importance of surveying deep‐water distributions

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(57 reference statements)
2
2
0
Order By: Relevance
“…As illustrated by our results (Figures 4-7), estimated ecological connectivity patterns are sensitive to assumptions regarding both the distributions of queen conch populations and their reproductive output. Thus, we highlight the need for updated demographic and habitat information for queen conch, strongly corroborating needs identified in previous studies (Prada et al, 2017;Kough et al, 2017;Truelove et al, 2017;Kitson-Walters et al, 2018;Boman et al, 2021). To refine larval connectivity estimates and fully understand conch demographics at both broad and smaller spatial scales within jurisdictionsthe following are needed: 1) representative surveys of conch population densities across a range of habitats, along with a precise understanding of the areas over which these densities can be extrapolated (Prada et al, 2017;Kough et al, 2017); 2) densities of individuals categorized as juveniles and adults and/ or detailed stock size structure reported; 3) detailed maps and/or areal estimates of conch habitat (i.e., areas where the species currently or has historically occurred) in each jurisdiction; and 4) surveys of conch populations located in depths below the typical range of fishing (i.e., >30m) to assess the contribution of mesophotic populations that might serve as deep refugia for shallow populations and which remain largely excluded from conch surveys (Boman et al, 2021).…”
Section: Management Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…As illustrated by our results (Figures 4-7), estimated ecological connectivity patterns are sensitive to assumptions regarding both the distributions of queen conch populations and their reproductive output. Thus, we highlight the need for updated demographic and habitat information for queen conch, strongly corroborating needs identified in previous studies (Prada et al, 2017;Kough et al, 2017;Truelove et al, 2017;Kitson-Walters et al, 2018;Boman et al, 2021). To refine larval connectivity estimates and fully understand conch demographics at both broad and smaller spatial scales within jurisdictionsthe following are needed: 1) representative surveys of conch population densities across a range of habitats, along with a precise understanding of the areas over which these densities can be extrapolated (Prada et al, 2017;Kough et al, 2017); 2) densities of individuals categorized as juveniles and adults and/ or detailed stock size structure reported; 3) detailed maps and/or areal estimates of conch habitat (i.e., areas where the species currently or has historically occurred) in each jurisdiction; and 4) surveys of conch populations located in depths below the typical range of fishing (i.e., >30m) to assess the contribution of mesophotic populations that might serve as deep refugia for shallow populations and which remain largely excluded from conch surveys (Boman et al, 2021).…”
Section: Management Implicationssupporting
confidence: 89%
“…Overall, our results support that estimates of contemporary demographic rates, and thus of fecundity, need to be considered for ecological connectivity studies (Lowe and Allendorf, 2010;Castorani et al, 2017;Johnston et al, 2018). Moreover, our results strongly corroborate advice for international management and conservation of queen conch, as well as research needs identified in previous conch studies (Prada et al, 2017;Kough et al, 2017;Stoner et al, 2019;Delgado and Glazer 2020;Boman et al, 2021). However, given the high likelihood of local settlement and distribution of distinct metapopulations, replenishment processes through larval dispersal are likely to occur only within the metapopulation spatial scales.…”
Section: Management Implicationssupporting
confidence: 88%
“…In The Bahamas and across the Caribbean, the best determinant of maturity in conch is a shell lip thickness of at least 15 mm (Boman et al, 2018); here, individuals with a lip thickness of at least 15 mm were categorized as adults and thinner lipped individuals as juveniles. Conch distributions are patchy (Boman et al, 2021), which interacted with the nonstandardized spatial effort during time‐based drift dives and required multiple terms to capture in statistical models (Kough et al, 2019). Here, the same negative binomial generalized linear model approach was used to explain variable counts of conch relative to continuous variables distance swept, maximum distance between individuals, and an interaction between the two, as well as a factor for surveys within the ECLSP (Kough et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Internal factors include species dispersal patterns and colonial breeding habits (Dormann, 2007). The second category is external environmental factors, which have their own pattern of spatial autocorrelation that they introduce into species data (Boman et al, 2021). Potential external factors include humidity, rainfall, and soil type.…”
Section: Previous Researchmentioning
confidence: 99%